2022
DOI: 10.1159/000527271
|View full text |Cite
|
Sign up to set email alerts
|

An Association Study of ESR1–XbaI and PvuII Gene Polymorphism in Migraine Susceptibility in the Jammu Region

Abstract: <b><i>Introduction:</i></b> Migraine is a neurovascular disorder and is clinically characterized by episodic attacks of mild to severe headaches. Due to the involvement of multiple environmental and genetic factors, it has become a much more complex neurological condition to understand. Apart from the environmental variables, a plethora of genes have been implicated, and one such example is <i>ESR</i>1. The present study was focused to find out the association of two importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…which was consistent with Kumar and group 29 in contrast to Ghosh and group 37 . The other intronic variant i.e., PvuII which is separated by the 50 bp from XbaI, two studies discussed the association in the respective populations, and upon combing both studies, the present pooled meta-analysis showed significant association with the risk of migraine including both of its clinical subtypes which supports the result observed by Joshi and group 14 in contrast to Kumar and group 29 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…which was consistent with Kumar and group 29 in contrast to Ghosh and group 37 . The other intronic variant i.e., PvuII which is separated by the 50 bp from XbaI, two studies discussed the association in the respective populations, and upon combing both studies, the present pooled meta-analysis showed significant association with the risk of migraine including both of its clinical subtypes which supports the result observed by Joshi and group 14 in contrast to Kumar and group 29 .…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we found two variants such as PvuII and XbaI of ESR1 studies in the Indian population by three different research groups 14 , 29 , 37 (Supplementary Tables 6 and 7 S1). Concerning ESR1-PvuII, a significant association has been found where the allele (OR: 1.47 [1.24–1.74], I 2 = 0%), dominant (OR: 1.66 [1.30–2.12], I 2 = 0%), and recessive model (OR: 1.91 [1.31–2.77], I 2 = 0%) significantly increase the risk of migraine.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…[15][16][17] It affects 2.7 percent to 10.0 percent of younger children (both sexes are affected equally), but as children get older, the female sex hormone affects more females (12 percent -17 percent) (Estrogen) and males with 4% -7%. 18,19 Migraine has multifactorial involvements including environment, genetic, 10,20 brain structure abnormalities, and their interaction 21 (Figure 3). The various pathological mechanism has been already established 20,22,23 but there are still matters of contention that what is the seed etiology of the condition.…”
Section: Introductionmentioning
confidence: 99%